MORPHOLOGICAL CHARACTERIZATION AND VARIETAL DELINEATION OF Vitellaria paradoxa (SHEA BUTTER) TREES FOUND ON THE UNIVERSITY OF ILORIN MAIN CAMPUS - Sale S.; Morakinyo J. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The present study reports on the morphological characterization and varietal delineation of Vitellaria paradoxa at the University of Ilorin Permanent Site. Forty trees were randomly sampled from two areas, (protected and disturbed), and used for this study. Thirty-eight descriptors, including both qualitative and quantitative variables, from growth forms and leaf descriptors to inflorescence and fruit descriptors, were used to assess the morphological variability. The data collected was subjected to R-software and SPSS version 16 for analysis. Result showed significant variation (P≤0.05) in quantitative morphological characteristics across the trees. There existed positive cross correlations (P≤0.05) between leaf blade length, leaf blade width and leaf petiole length. Dendrogram constructed using Average Linkage Groups from these characters produced eight cluster groups, each with distinctive characteristics that differentiated them from the other groups. These groups could serve as local shea varieties in the study area and could be a base for any Vitellaria development and breeding programmes.